Brief communication: A re‐evaluation of the health index of southern Brazilian shellmound populations. Issue 2 (1st November 2017) - Hubbe, Mark; Green, Madelyn K.; Cheverko, Colleen M.; Neves, Walter A.
Abstract: Objectives: The southern Brazilian shellmounds provide archaeological evidence of prolonged human activity in the coast from approximately 6000 to 1000 BP. Shellmound building populations exploited the rich coastal estuarine zones, and the human remains recovered from them are important sources of information on health and overall lifestyle of these mid‐Holocene groups. Therefore, they were included in the Western Hemisphere Global History of Health project. The shellmounds contribute the highest Health Index in the Western Hemisphere, but these conclusions are based on collections that exclude postcranial remains. Here, we reconstruct the Health Index for one specific shellmound using both cranial and postcranial remains to determine whether the initial studies might misrepresent the relative health of the Brazilian shellmound builders. Materials and methods: The Health Index was calculated for a sample of 18 complete skeletons recovered from the shellmound Porto do Rio Vermelho 02 (Santa Catarina Island, Brazil). The Heath Index was calculated with and without postcranial markers and the results are compared with the Western Hemisphere Global History of Health data. Results: The Health Index for Porto do Rio Vermelho 02 is lower than the reported average for American series in the Western Hemisphere Global History of Health Project and considerably lower than the original index reported for Brazilian shellmounds. This discrepancy is due to an increased prevalence of infectious disease and low stature. Conclusions: Although the Health Index remains a useful comparison statistic, re‐evaluation of fragmentary skeletal remains demonstrates the need for caution when applying it to incomplete skeletal series.